Acute Cholecystitis in Aged Patients. Issue 3 (1996) - Prousalidis, J.; Fahadidis, E.; Apostolidis, S.; Katsohis, C.; Aletras, H.
Abstract : The aim ofthis study is the analysis ofthe results in 62 patients over 70 years ofage with acute cholecystitis treated in our Department from 1970 to 1990. The clinical picture in 47 patients was mild and in 15 severe. In 14 cases (10 calculous, 4 acalculous) the acute cholecystitis subsided with antibiotics (Group A). In 48 more cases (45 calculous, 3 acalculous) following 1-3 days conservative treatment, operation was undertaken. Besides acute cholystitis there was gangrene of gallbladder in 10, choledocholithiasis in 7 and choloperitoneum without perforation in 7 cases. Cholecystostomy in 25, cholecystectomy in 15 and cholecystectomy with exploration ofthe bill duct in 8 cases was performed (Group B). There was one death in group A and 3 deaths .in group B. The hospital stay was 20 days. In conclusion the clinical findings in acute cholecystitis in the aged are usually mild. In the case of failure of medical treatment, after 2-3 days emergency surgery should be performed.